Examining the Neural Processes of Valence-Dependent Feedback Processing and Practice-Related Changes in Extensive Motor Learning - Margraf, Linda; Krause, Daniel; Weigelt, Matthias

Surprising effects of frontal neural correlates of augmented feedback-processing in extensive motor learning - Margraf, Linda; Krause, Daniel; Weigelt, Matthias

Professionswissen von angehenden Sportlehrkräften zur Gestaltung ei-nes bewegungsorientierten Schulalltags. Eine empirische Untersuchung im Bereich des Professionswissens von Lehrpersonen. - Satzinger, Nicole
Forschungsarbeiten zum Professionswissen von Sportlehrer*innen beschränkt sich weitgehend auf den Sportunterricht. Dem außerunterrichtlichen Schulsport wurde bisher wenig Aufmerksamkeit geschenkt. Hier setzt die vorliegende Arbeit an, die sich auf das Professionswissen von Sportlehrer*innen zur Gestaltung eines bewegungsorientierten Schulalltags konzentriert. Als theoretische Rahmung liegen den Überlegungen das Kompetenzmodell von Baumert und Kunter (2011) und das Zahnradmodell der "Bewegten Schule" von Städler (2016) zugrunde. Die empirische Untersuchung basiert auf einem dreistufigen Vorgehen. Zuerst wurde im Rahmen von fünf Fokusgruppeninterviews mit Expert*innen die aus Praxissicht relevanten Wissensfacetten des Professionswissens zur Gestaltung eines bewegungsorientierten Schulalltags erhoben. Die Auswertung erfolgte auf Basis der qualitativen Inhaltsanalyse nach Mayring (2015). Darauf aufbauend wurden die Facetten in einer Fragebogenerhebung von Expert*innen hinsichtlich ihrer jeweiligen Relevanz bewertet, anschließend wurden die Ergebnisse bilanzierend zusammengeführt. Es konnten 46 Wissensfacetten des Professionswissens identifiziert werden, die in 11 übergreifenden Kategorien geclustert wurden. Die Bereiche des Professionswissens nach Baumert und Kunter (2011) werden vollständig abgebildet und eine Zuordnung dem Zahnradmodell von Städler (2016) fand statt. Ein Professionswissen im Bereich Organisation und Beratung scheint relevant zur Gestaltung eines bewegungsorientierten Schulalltags zu sein. Die Erkenntnisse können als Ansatzpunkt für Forschungsarbeiten sowie für die universitäre Ausbildung dienen.
Keywords: Professionswissen; Sportlehrerausbildung

A longitudinal analysis of reciprocal relationships between actual and perceived motor competencies and physical self-concept in primary-school age children - Strotmeyer, Anne; Herrmann, Christian; Kehne, Miriam (Psychology of Sport and Exercise)
Physical self-concept (PSC) and motor competencies are important factors in view of the development of a physically active lifestyle. There are research gaps regarding longitudinal studies of these relationships. This article presents findings of a longitudinal study (n = 200; 58% girls, M = 8.84 ± 0.63 years) at three primary schools. The aim of this study was to analyze the relationship between actual motor competencies (AMC) and perceived motor competencies (PMC) and PSC. Therefore, manifest path models in cross-lagged design were performed. Results show that correlations between PMC and AMC increased over time and were stronger in object control than in locomotor. Effects of AMC on PSC were more strongly mediated by PMC in object control than in locomotor. To promote physical activity, developing strategies should be aimed at the acquisition of AMC, particularly in object control, and PMC, especially in locomotor, during childhood.
Keywords: Applied Psychology

Gesundheit und Stress im Studium - Bedeutung gesundheitsrelevanter Lebensstile - Waltert, Carolin

Die ausgekugelte Schulter im Kanusport. Behandlung und Vorbeugen - Bauer, A.; Buhmann, H. W.; Güldenpenning, Iris (Kanusport)

Produktionskosten von Täuschungshandlungen im Sport: Der Einfluss von Übung auf die Durchführung von Blicktäuschungen im Basketball - Böer, Nils Tobias; Weigelt, Matthias; Schütz, Christoph; Güldenpenning, Iris (Ein Gehirn, viel Bewegung – Variabilität und Plastizität über die Lebensspanne. Abstractband der 54. Jahrestagung der Arbeitsgemeinschaft für Sportpsychologie (asp))

Producing deceptive actions in sports: The costs of generating head fakes in basketball - Böer, Nils Tobias; Güldenpenning, Iris; Kunde, Wilfried; Weigelt, Matthias (Abstracts of the 64th Conference of Experimental Psychologists (TeaP))

Kognitive Grundlagen von Täuschungshandlungen im Sport - Weigelt, Matthias; Güldenpenning, Iris (Kognition und Motorik: Sportpsychologische Grundlagen und Anwendungen im Sport)

Das Stützpunktsystem im paralympischen Leistungssport. Eine empirische Studie unter Berücksichtigung der Perspektive von Para-Athletinnen und -Athleten sowie des Stützpunktpersonals. - Radtke, Sabine; Freier, M. Pia
Keywords: Para Sport

Betriebliche Gesundheitsförderung: Ein leeres Versprechen? - Auer, Thorsten Fabian; Sennefelder, Lisa; Meier, Heiko (Public Health Forum)
Unternehmen investieren zunehmend in Angebote Betrieblicher Gesundheitsförderung (BGF). Dabei stellt sich die Frage nach dem Kosten-Nutzen-Verhältnis jenseits des individuellen Nutzens durch die Förderung der Mitarbeitergesundheit. Deshalb wurden im Rahmen einer Sekundäranalyse Effekte der BGF auf den Unternehmenserfolg berechnet. Die Ergebnisse lassen vermuten, dass sich eine verhaltensorientierte BGF kaum positiv auf die Arbeitsproduktivität und Kommunikationsstruktur in Unternehmen auswirkt.
Keywords: Kommunikation; Arbeitsproduktivität; Betriebliche Gesundheitsförderung; Kosten-Nutzen-Verhältnis

Editorial: Netzwerke und Vernetzung im Sport - Meier, Heiko; Kukuk, Marc; Riedl, Lars (Sport und Gesellschaft)
Keywords: Philosophy; Social Sciences (miscellaneous); History

Vereinzelung oder Gemeinschaftsbildung: Was passiert an Calisthenics-Anlagen? - Meier, Heiko; Kukuk, Marc; Schmieding, Ruben (Playground@Landscape)

Die Bedeutung und Funktion sportlicher Aktivitäten im Gesundheitsmanagement der öffentlichen Verwaltungen - Barrieren und Gelingensbedingungen. - Sennefelder, Lisa

Wie passen Vertrauen, Kontrolle und Hierarchie zusammen? Ein erlebnispädagogisch orientiertes Konzept zum Aufbau einer Vertrauenskultur in Verwaltungsorganisationen - Sennefelder, Lisa; Meier, Heiko

Vertrauen im Sport – mehr als nur ein No-Look-Pass - Meier, Heiko (Facetten des Vertrauens und Misstrauens)
Ohne ständig thematisiert zu werden, kommt Vertrauen im Sport immer eine große Bedeutung zu, sei es beim No-look-Pass, bei der Hilfestellung im Turnen oder im Klettersport. Mehr noch: Ohne Vertrauensgrundlage ist Sport praktisch oftmals unmöglich. Umgekehrt wiegen Vertrauensbrüche schwer. Sie gefährden Sportarten, Sportorganisationen und Personen. Damit ist der Aufbau von Vertrauen offensichtlich für den Sport konstitutiv. Der Beitrag untersucht deshalb, wie Vertrauen im Sport nicht nur soziale Verhältnisse und Beziehungen umrahmt, sondern sie konstituiert, und inwiefern sich der Sport diesbezüglich von anderen gesellschaftlichen Kontexten unterscheidet. Dazu wird unter Rückgriff auf Niklas Luhmanns Unterscheidung zwischen Person- und Systemvertrauen der Sportverein dahingehend analysiert, wie bedeutsam und wie funktional Vertrauen für dessen Selbstorganisation und Systemerhalt ist. Dies führt zu dem Vorschlag, Vertrauen im Sportverein als Steuerungsinstrument anzusehen, welches in einer spezifischen Symbolik zum Ausdruck kommt.

"Und dann muss es gelebt werden!" - Der Sport im Gesundheitsmanagement öffentlicher Verwaltungen - Sennefelder, Lisa

Vertrauen in der öffentlichen Verwaltung - Sennefelder, Lisa

Exploring intensity-dependent modulations in EEG resting-state network efficiency induced by exercise - Büchel, Daniel; Sandbakk, Øyvind; Baumeister, Jochen (European Journal of Applied Physiology)
Abstract Purpose Exhaustive cardiovascular load can affect neural processing and is associated with decreases in sensorimotor performance. The purpose of this study was to explore intensity-dependent modulations in brain network efficiency in response to treadmill running assessed from resting-state electroencephalography (EEG) measures. Methods Sixteen trained participants were tested for individual peak oxygen uptake (VO 2 peak ) and performed an incremental treadmill exercise at 50% (10 min), 70% (10 min) and 90% speed VO 2 peak (all-out) followed by cool-down running and active recovery. Before the experiment and after each stage, borg scale (BS), blood lactate concentration (B La ), resting heartrate (HR rest ) and 64-channel EEG resting state were assessed. To analyze network efficiency, graph theory was applied to derive small world index (SWI) from EEG data in theta, alpha-1 and alpha-2 frequency bands. Results Analysis of variance for repeated measures revealed significant main effects for intensity on BS, B La , HR rest and SWI. While BS, B La and HR rest indicated maxima after all-out, SWI showed a reduction in the theta network after all-out. Conclusion Our explorative approach suggests intensity-dependent modulations of resting-state brain networks, since exhaustive exercise temporarily reduces brain network efficiency. Resting-state network assessment may prospectively play a role in training monitoring by displaying the readiness and efficiency of the central nervous system in different training situations.

Stance leg and surface stability modulate cortical activity during human single leg stance - Büchel, Daniel; Lehmann, Tim; Ullrich, Sarah; Cockcroft, John; Louw, Quinette; Baumeister, Jochen (Experimental Brain Research)
Abstract Mobile Electroencephalography (EEG) provides insights into cortical contributions to postural control. Although changes in theta (4–8 Hz) and alpha frequency power (8–12 Hz) were shown to reflect attentional and sensorimotor processing during balance tasks, information about the effect of stance leg on cortical processing related to postural control is lacking. Therefore, the aim was to examine patterns of cortical activity during single-leg stance with varying surface stability. EEG and force plate data from 21 healthy males (22.43 ± 2.23 years) was recorded during unipedal stance (left/right) on a stable and unstable surface. Using source-space analysis, power spectral density was analyzed in the theta, alpha-1 (8–10 Hz) and alpha-2 (10–12 Hz) frequency bands. Repeated measures ANOVA with the factors leg and surface stability revealed significant interaction effects in the left ( p = 0.045, η p 2 = 0.13) and right motor clusters ( F = 16.156; p = 0.001, η p 2 = 0.41). Furthermore, significant main effects for surface stability were observed for the fronto-central cluster (theta), left and right motor (alpha-1), as well as for the right parieto-occipital cluster (alpha-1/alpha-2). Leg dependent changes in alpha-2 power may indicate lateralized patterns of cortical processing in motor areas during single-leg stance. Future studies may therefore consider lateralized patterns of cortical activity for the interpretation of postural deficiencies in unilateral lower limb injuries.

Functional Cortical Connectivity Related to Postural Control in Patients Six Weeks After Anterior Cruciate Ligament Reconstruction - Lehmann, Tim; Büchel, Daniel; Mouton, Caroline; Gokeler, Alli; Seil, Romain; Baumeister, Jochen (Frontiers in Human Neuroscience)
Whereas initial findings have already identified cortical patterns accompanying proprioceptive deficiencies in patients after anterior cruciate ligament reconstruction (ACLR), little is known about compensatory sensorimotor mechanisms for re-establishing postural control. Therefore, the aim of the present study was to explore leg dependent patterns of cortical contributions to postural control in patients 6 weeks following ACLR. A total of 12 patients after ACLR (25.1 ± 3.2 years, 178.1 ± 9.7 cm, 77.5 ± 14.4 kg) and another 12 gender, age, and activity matched healthy controls participated in this study. All subjects performed 10 × 30 s. single leg stances on each leg, equipped with 64-channel mobile electroencephalography (EEG). Postural stability was quantified by area of sway and sway velocity. Estimations of the weighted phase lag index were conducted as a cortical measure of functional connectivity. The findings showed significant group × leg interactions for increased functional connectivity in the anterior cruciate ligament (ACL) injured leg, predominantly including fronto−parietal [ F (1, 22) = 8.41, p ≤ 0.008, η 2 = 0.28], fronto−occipital [ F (1, 22) = 4.43, p ≤ 0.047, η 2 = 0.17], parieto−motor [ F (1, 22) = 10.30, p ≤ 0.004, η 2 = 0.32], occipito−motor [ F (1, 22) = 5.21, p ≤ 0.032, η 2 = 0.19], and occipito−parietal [ F (1, 22) = 4.60, p ≤ 0.043, η 2 = 0.17] intra−hemispherical connections in the contralateral hemisphere and occipito−motor [ F (1, 22) = 7.33, p ≤ 0.013, η 2 = 0.25] on the ipsilateral hemisphere to the injured leg. Higher functional connectivity in patients after ACLR, attained by increased emphasis of functional connections incorporating the somatosensory and visual areas, may serve as a compensatory mechanism to control postural stability of the injured leg in the early phase of rehabilitation. These preliminary results may help to develop new neurophysiological assessments for detecting functional deficiencies after ACLR in the future.

EEG-derived brain graphs are reliable measures for exploring exercise-induced changes in brain networks - Büchel, Daniel; Lehmann, Tim; Sandbakk, Øyvind; Baumeister, Jochen (Scientific Reports)
Abstract The interaction of acute exercise and the central nervous system evokes increasing interest in interdisciplinary research fields of neuroscience. Novel approaches allow to monitor large-scale brain networks from mobile electroencephalography (EEG) applying graph theory, but it is yet uncertain whether brain graphs extracted after exercise are reliable. We therefore aimed to investigate brain graph reliability extracted from resting state EEG data before and after submaximal exercise twice within one week in male participants. To obtain graph measures, we extracted global small-world-index (SWI), clustering coefficient (CC) and characteristic path length (PL) based on weighted phase leg index (wPLI) and spectral coherence (Coh) calculation. For reliability analysis, Intraclass-Correlation-Coefficient (ICC) and Coefficient of Variation (CoV) were computed for graph measures before (REST) and after POST) exercise. Overall results revealed poor to excellent measures at PRE and good to excellent ICCs at POST in the theta, alpha-1 and alpha-2, beta-1 and beta-2 frequency band. Based on bootstrap-analysis, a positive effect of exercise on reliability of wPLI based measures was observed, while exercise induced a negative effect on reliability of Coh-based graph measures. Findings indicate that brain graphs are a reliable tool to analyze brain networks in exercise contexts, which might be related to the neuroregulating effect of exercise inducing functional connections within the connectome. Relative and absolute reliability demonstrated good to excellent reliability after exercise. Chosen graph measures may not only allow analysis of acute, but also longitudinal studies in exercise-scientific contexts.

Stance leg and surface stability modulate cortical activity during human single leg stance - Büchel, Daniel; Lehmann, Tim; Ullrich, Sarah; Cockcroft, John; Louw, Quinette; Baumeister, Jochen (Experimental Brain Research)

Mentale Rotationsleistungen bei der Betrachtung und Umsetzung von Spielzügen im Basketball: Novizen vs. erfahrene Basketballspieler - Krause, Daniel; Behrens, J.B.; Löhers, L.; Weigelt, Matthias

Representations after mentally practiced one finger sequences are effector independent - Dahm, Stephan; Weigelt, Matthias; Rieger, M.

Mental body rotation with egocentric and object-based transformations in different postures: sitting vs. standing - Budde, Kirsten; Barela, J.A.; Figueiredo, G.A.; Weigelt, Matthias

How does spectator presence affect football? Home advantage remains in European top-class football matches played without spectators during the COVID-19 pandemic - Wunderlich, Fabian; Weigelt, Matthias; Rein, Robert; Memmert, Daniel (PLOS ONE)
The present paper investigates factors contributing to the home advantage, by using the exceptional opportunity to study professional football matches played in the absence of spectators due to the COVID-19 pandemic in 2020. More than 40,000 matches before and during the pandemic, including more than 1,000 professional matches without spectators across the main European football leagues, have been analyzed. Results support the notion of a crowd-induced referee bias as the increased sanctioning of away teams disappears in the absence of spectators with regard to fouls (p < .001), yellow cards (p < .001), and red cards (p < .05). Moreover, the match dominance of home teams decreases significantly as indicated by shots (p < .001) and shots on target (p < .01). In terms of the home advantage itself, surprisingly, only a non-significant decrease is found. While the present paper supports prior research with regard to a crowd-induced referee bias, spectators thus do not seem to be the main driving factor of the home advantage. Results from amateur football, being naturally played in absence of a crowd, provide further evidence that the home advantage is predominantly caused by factors not directly or indirectly attributable to a noteworthy number of spectators.
Keywords: Multidisciplinary

Mental body rotation with egocentric and object-based transformations in different postures: standing vs. balancing - Budde, Kirsten; Jöllenbeck, Thomas; Barela, José A.; Figueiredo, Gabriella A.; Weigelt, Matthias (Brazilian Journal of Motor Behavior)
BACKGROUND: Previous studies suggest better visual-spatial processing when participants are tested in postures in which dynamic stability is challenged. The question arises if this is also true for the performance in mental body-rotation tasks (MBRT). AIM: Taking the embodied cognition approach into account, the first aim of the present study was to examine the potential influence of different demands on dynamic stability for two postures (parallel stand vs. tandem stand) on solving two versions of the MBRT, inducing either an object-based or an egocentric perspective transformation strategy. The second aim was to investigate if these different demands on dynamic stability are reflected in postural sway parameters. METHOD: Thirty participants (18 females and 12 males) were tested in the two MBRTs and in a control condition. All tasks were performed while standing on a balance beam in tandem stand and in a feet parallel position on a force plate. RESULTS: The results for response time and response error revealed effects of rotation angle and task, but no effect of posture. The analyzed Center of Pressure (CoP) data revealed a reduction of body sway during the MBRT for egocentric perspective transformations. CONCLUSION: The results indicate that participants performed better for egocentric than for object-based transformations and that the egocentric transformation leads to more postural stability than the object-based.
Keywords: General Engineering

Neurophysiology of embodied mental rotation: Event‐related potentials in a mental rotation task with human bodies as compared to alphanumeric stimuli - Krause, Daniel; Richert, Benjamin; Weigelt, Matthias (European Journal of Neuroscience)
Keywords: General Neuroscience

An interrater reliability study of gait analysis systems with the dual task paradigm in healthy young and older adults - Klotzbier, Thomas Jürgen; Wollesen, Bettina; Vogel, Oliver; Rudisch, Julian; Cordes, Thomas; Jöllenbeck, Thomas; Vogt, Lutz (European Review of Aging and Physical Activity)
Abstract Background and aims One reason for the controversial discussion of whether the dual task (DT) walking paradigm has an added value for diagnosis in clinical conditions might be the use of different gait measurement systems. Therefore, the purpose was 1) to detect DT effects of central gait parameters obtained from five different gait analysis devices in young and old adults, 2) to assess the consistency of the measurement systems, and 3) to determine if the absolut and proportional DT costs (DTC) are greater than the system-measurement error under ST. Methods Twelve old (72.2 ± 7.9y) and 14 young adults (28.3 ± 6.2y) walked a 14.7-m distance under ST and DT at a self-selected gait velocity. Interrater reliability, precision of the measurement and sensitivity to change were calculated under ST and DT. Results An age effect was observed in almost all gait parameters for the ST condition. For DT only differences for stride length ( p < .029, ɳ 2 p = .239) as well as single and double limb support ( p = .036, ɳ 2 p = .227; p = .034, ɳ 2 p = .218) remained. The measurement systems showed a lower absolute agreement compared to consistency across all systems. Conclusions When reporting DT effects, the real changes in performance and random measurement errors should always be accounted for. These findings have strong implications for interpreting DT effects.
Keywords: Geriatrics and Gerontology

Agreement and consistency of five different clinical gait analysis systems in the assessment of spatiotemporal gait parameters - Rudisch, Julian; Jöllenbeck, Thomas; Vogt, Lutz; Cordes, Thomas; Klotzbier, Thomas Jürgen; Vogel, Oliver; Wollesen, Bettina (Gait & Posture)
Keywords: Rehabilitation; Orthopedics and Sports Medicine; Biophysics

Learning to play golf for elderly people with subjective memory complaints: feasibility of a single‐blinded randomized pilot trial - Stroehlein, Julia K.; Vieluf, Solveig; Zimmer, Philipp; Schenk, Alexander; Oberste, Max; Gölz, Christian Johannes; van den Bongard, Franziska; Reinsberger, Claus (BMC Neurology)
Abstract Background Subjective Memory Complaints (SMC) in elderly people due to preclinical Alzheimer’s Disease may be associated with dysregulation of the Kynurenine Pathway (KP), with an increase in neurotoxic metabolites that affect cognition. Golf is a challenging sport with high demands on motor, sensory, and cognitive abilities, which might bear the potential to attenuate the pathological changes of preclinical AD. This trial investigated the feasibility of learning to play golf for elderly with cognitive problems and its effects on cognitive functions and the KP. Methods In a 22-week single-blinded randomized controlled trial, elderly people with SMC were allocated to the golf ( n = 25, 180 min training/week) or control group ( n = 21). Primary outcomes were feasibility (golf exam, adherence, adverse events) and general cognitive function (Alzheimer’s Disease Assessment Scale). Secondary outcomes include specific cognitive functions (Response Inhibition, Corsi Block Tapping Test, Trail Making Test), KP metabolites and physical performance (6-Minute-Walk-Test). Baseline-adjusted Analysis-of-Covariance was conducted for each outcome. Results 42 participants were analyzed. All participants that underwent the golf exam after the intervention passed it (20/23). Attendance rate of the golf intervention was 75 %. No adverse events or drop-outs related to the intervention occurred. A significant time*group interaction ( p = 0.012, F = 7.050, Cohen’s d = 0.89) was found for correct responses on the Response Inhibition task, but not for ADAS-Cog. Moreover, a significant time*group interaction for Quinolinic acid to Tryptophan ratios ( p = 0.022, F = 5.769, Cohen’s d = 0.84) in favor of the golf group was observed. An uncorrected negative correlation between attendance rate and delta Quinolinic acid to Kynurenic acid ratios in the golf group ( p = 0.039, r =-0.443) was found as well. Conclusions The findings indicate that learning golf is feasible and safe for elderly people with cognitive problems. Preliminary results suggest positive effects on attention and the KP. To explore the whole potential of golfing and its effect on cognitive decline, a larger cohort should be studied over a longer period with higher cardiovascular demands. Trial registration The trial was retrospectively registered (2nd July 2018) at the German Clinical Trials Register ( DRKS00014921 ).
Keywords: Clinical Neurology; General Medicine

Generalized tonic-clonic seizures are accompanied by changes of interrelations within the autonomic nervous system. - Vieluf, S; Hasija, Tanuj; Schreier, PJ; El Atrache, R; Hammond, S; Mohammadpour Touserkani, F; Sarkis, RA; Loddenkemper, T; Reinsberger, Claus (Epilepsy Behav)

Electrophysiological signatures of dedifferentiation differ between fit and less fit older adults - Gölz, Christian Johannes; Mora, Karin; Stroehlein, Julia Kristin; Haase, Franziska Katharina; Dellnitz, Michael; Reinsberger, Claus; Vieluf, Solveig (Cognitive Neurodynamics)
Abstract Cardiorespiratory fitness was found to influence age-related changes of resting state brain network organization. However, the influence on dedifferentiated involvement of wider and more unspecialized brain regions during task completion is barely understood. We analyzed EEG data recorded during rest and different tasks (sensory, motor, cognitive) with dynamic mode decomposition, which accounts for topological characteristics as well as temporal dynamics of brain networks. As a main feature the dominant spatio-temporal EEG pattern was extracted in multiple frequency bands per participant. To deduce a pattern’s stability, we calculated its proportion of total variance among all activation patterns over time for each task. By comparing fit (N = 15) and less fit older adults (N = 16) characterized by their performance on a 6-min walking test, we found signs of a lower task specificity of the obtained network features for the less fit compared to the fit group. This was indicated by fewer significant differences between tasks in the theta and high beta frequency band in the less fit group. Repeated measures ANOVA revealed that a significantly lower proportion of total variance can be explained by the main pattern in high beta frequency range for the less fit compared to the fit group [F(1,29) = 12.572, p = .001, partial η 2 = .300]. Our results indicate that the dedifferentiation in task-related brain activation is lower in fit compared to less fit older adults. Thus, our study supports the idea that cardiorespiratory fitness influences task-related brain network organization in different task domains.
Keywords: Cognitive Neuroscience

Classification of visuomotor tasks based on electroencephalographic data depends on age-related differences in brain activity patterns - Gölz, Christian Johannes; Mora, K.; Rudisch, J.; Gaidai, Roman; Reuter, E.; Godde, B.; Reinsberger, Claus; Voelcker-Rehage, C.; Vieluf, S. (Neural Networks)
Keywords: Artificial Intelligence; Cognitive Neuroscience

Classification of visuomotor tasks based on electroencephalographic data depends on age-related differences in brain activity patterns - Goelz, C.; Mora, K.; Rudisch, J.; Gaidai, R.; Reuter, E.; Godde, B.; Reinsberger, Claus; Voelcker-Rehage, C.; Vieluf, S. (Neural Networks)
Keywords: Artificial Intelligence; Cognitive Neuroscience

Twenty-four-hour patterns in electrodermal activity recordings of patients with and without epileptic seizures. - Vieluf, S; Amengual-Gual, M; Zhang, B; El Atrache, R; Ufongene, C; Jackson, MC; Branch, S; Reinsberger, Claus; Loddenkemper, T (Epilepsia)

Exercise and sports after COVID-19-Guidance from a clinical perspective. - Halle, M; Bloch, W; Niess, AM; Predel, HG; Reinsberger, Claus; Scharhag, J; Steinacker, J; Wolfarth, B; Scherr, J; Niebauer, J (Transl Sports Med)

The effects of repetitive head impacts on postural control: A systematic review. - Bonke, EM; Southard, J; Buckley, TA; Reinsberger, Claus; Koerte, IK; Howell, DR (J Sci Med Sport)

Head injuries in professional football (soccer): Results of video analysis verified by an accident insurance registry. - Krutsch, V; Krutsch, W; Härtl, J; Bloch, H; Alt, V; Klein, C; Reinsberger, Claus; Seiffert, R; Huber, L; Weber, J (PLoS One)

Evaluation of Open-Source and Pre-Trained Deep Convolutional Neural Networks Suitable for Player Detection and Motion Analysis in Squash. - Brumann, C; Kukuk, M; Reinsberger, Claus (Sensors (Basel))

PIVOT: A Parsimonious End-to-End Learning Framework for Valuing Player Actions in Handball using Tracking Data - Müller, Oliver; Caron, Matthew; Döring, Michael; Heuwinkel, Tim; Baumeister, Jochen (8th Workshop on Machine Learning and Data Mining for Sports Analytics (ECML PKDD 2021))
Over the last years, several approaches for the data-driven estimation of expected possession value (EPV) in basketball and association football (soccer) have been proposed. In this paper, we develop and evaluate PIVOT: the first such framework for team handball. Accounting for the fast-paced, dynamic nature and relative data scarcity of hand- ball, we propose a parsimonious end-to-end deep learning architecture that relies solely on tracking data. This efficient approach is capable of predicting the probability that a team will score within the near future given the fine-grained spatio-temporal distribution of all players and the ball over the last seconds of the game. Our experiments indicate that PIVOT is able to produce accurate and calibrated probability estimates, even when trained on a relatively small dataset. We also showcase two interactive applications of PIVOT for valuing actual and counterfactual player decisions and actions in real-time.
Keywords: expected possession value; handball; tracking data; time series classification; deep learning

Somatosensory perturbations influence cortical activity associated with single-limb balance performance - Sherman, David A.; Lehmann, Tim; Baumeister, Jochen; Grooms, Dustin R.; Norte, Grant E. (Experimental Brain Research)
Keywords: General Neuroscience

External Focus of Attention Influences Cortical Activity Associated with Single Limb Balance Performance - Sherman, David A; Lehmann, Tim; Baumeister, Jochen; Gokeler, Alli; Donovan, Luke; Norte, Grant E (Physical Therapy)
Abstract Objective External focus (EF) of attention leads to improved balance performance. Consideration of the neuromodulatory effects of EF may inform its clinical utility in addressing neuroplastic impairments after musculoskeletal injuries. We aimed to determine whether electrocortical activity and balance performance changed with attentional foci that prioritized differing sensory feedback and whether changes in electrocortical activity and balance were associated. Methods Individuals who were healthy (n = 15) performed a single-limb balance task under 3 conditions: internal focus (IF), somatosensory focus [EF with a baton (EF-baton)], and visual focus [EF with a laser (EF-laser)]. Electrocortical activity and postural sway were recorded concurrently using electroencephalography and a triaxial force plate. Electroencephalographic signals were decomposed, localized, and clustered to generate power spectral density in θ and α-2 frequency bands. Postural sway signals were analyzed with center-of-pressure sway metrics (eg, area, distance, velocity) and knee angle. The relationship between percent change in clustered brain activity and task performance metrics was assessed. Results Both EF conditions resulted in increased cortical activity and improved balance performance compared to IF. EF-laser had the largest effect, demonstrating increased frontal θ power (d = 0.64), decreased central θ power (d = −0.30), and decreased bilateral motor, bilateral parietal, and occipital α-2 power (d = −1.38 to −4.27) as well as a shorter path distance (d = −0.94) and a deeper (d = 0.70) and less variable (d = −1.15) knee angle than IF. Weak to moderate associations exist between increases in cortical activity and improved balance performance (ρ = 0.405–0.584). Conclusions EF resulted in increased cortical activity associated with cognitive, motor, somatosensory, and visual processing. EF-laser, which prioritized visual feedback, had the largest and broadest effects. Changes in cortical activity resulting from EF were independently associated with improved balance performance. Impact This study demonstrates that goal-oriented attention results in functional increases in brain activity compared to internally directed self-focus. These results suggest EF may target neurophysiologic impairments and improve balance in clinical populations.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation

Functional Cortical Connectivity Related to Postural Control in Patients Six Weeks After Anterior Cruciate Ligament Reconstruction - Lehmann, Tim; Büchel, Daniel; Mouton, Caroline; Gokeler, Alli; Seil, Romain; Baumeister, Jochen (Frontiers in Human Neuroscience)
Whereas initial findings have already identified cortical patterns accompanying proprioceptive deficiencies in patients after anterior cruciate ligament reconstruction (ACLR), little is known about compensatory sensorimotor mechanisms for re-establishing postural control. Therefore, the aim of the present study was to explore leg dependent patterns of cortical contributions to postural control in patients 6 weeks following ACLR. A total of 12 patients after ACLR (25.1 ± 3.2 years, 178.1 ± 9.7 cm, 77.5 ± 14.4 kg) and another 12 gender, age, and activity matched healthy controls participated in this study. All subjects performed 10 × 30 s. single leg stances on each leg, equipped with 64-channel mobile electroencephalography (EEG). Postural stability was quantified by area of sway and sway velocity. Estimations of the weighted phase lag index were conducted as a cortical measure of functional connectivity. The findings showed significant group × leg interactions for increased functional connectivity in the anterior cruciate ligament (ACL) injured leg, predominantly including fronto−parietal [ F (1, 22) = 8.41, p ≤ 0.008, η 2 = 0.28], fronto−occipital [ F (1, 22) = 4.43, p ≤ 0.047, η 2 = 0.17], parieto−motor [ F (1, 22) = 10.30, p ≤ 0.004, η 2 = 0.32], occipito−motor [ F (1, 22) = 5.21, p ≤ 0.032, η 2 = 0.19], and occipito−parietal [ F (1, 22) = 4.60, p ≤ 0.043, η 2 = 0.17] intra−hemispherical connections in the contralateral hemisphere and occipito−motor [ F (1, 22) = 7.33, p ≤ 0.013, η 2 = 0.25] on the ipsilateral hemisphere to the injured leg. Higher functional connectivity in patients after ACLR, attained by increased emphasis of functional connections incorporating the somatosensory and visual areas, may serve as a compensatory mechanism to control postural stability of the injured leg in the early phase of rehabilitation. These preliminary results may help to develop new neurophysiological assessments for detecting functional deficiencies after ACLR in the future.
Keywords: Behavioral Neuroscience; Biological Psychiatry; Psychiatry and Mental health; Neurology; Neuropsychology and Physiological Psychology

Stance leg and surface stability modulate cortical activity during human single leg stance - Büchel, Daniel; Lehmann, Tim; Ullrich, Sarah; Cockcroft, John; Louw, Quinette; Baumeister, Jochen (Experimental Brain Research)
Abstract Mobile Electroencephalography (EEG) provides insights into cortical contributions to postural control. Although changes in theta (4–8 Hz) and alpha frequency power (8–12 Hz) were shown to reflect attentional and sensorimotor processing during balance tasks, information about the effect of stance leg on cortical processing related to postural control is lacking. Therefore, the aim was to examine patterns of cortical activity during single-leg stance with varying surface stability. EEG and force plate data from 21 healthy males (22.43 ± 2.23 years) was recorded during unipedal stance (left/right) on a stable and unstable surface. Using source-space analysis, power spectral density was analyzed in the theta, alpha-1 (8–10 Hz) and alpha-2 (10–12 Hz) frequency bands. Repeated measures ANOVA with the factors leg and surface stability revealed significant interaction effects in the left ( p = 0.045, η p 2 = 0.13) and right motor clusters ( F = 16.156; p = 0.001, η p 2 = 0.41). Furthermore, significant main effects for surface stability were observed for the fronto-central cluster (theta), left and right motor (alpha-1), as well as for the right parieto-occipital cluster (alpha-1/alpha-2). Leg dependent changes in alpha-2 power may indicate lateralized patterns of cortical processing in motor areas during single-leg stance. Future studies may therefore consider lateralized patterns of cortical activity for the interpretation of postural deficiencies in unilateral lower limb injuries.
Keywords: General Neuroscience

EEG‑derived brain graphs are reliable measures for exploring exercise‑induced changes in brain networks - Büchel, Daniel; Lehmann, Tim; Sandbakk, Øyvind; Baumeister, Jochen (Scientific Reports)
Keywords: Multidisciplinary

Bewegungsförderung in Ganztagsschulen - Möhring, Julia; Krumhöfner, Anika; Gräfin von Plettenberg, Elisabeth Gudila Sophia Ida Maria (-)

Wettkampfbezogene Emotionen im Sport – ein Scoping-Review - Wetzel, Änne; Güldenpenning, Iris; Weigelt, Matthias (German Journal of Exercise and Sport Research)
Zusammenfassung Jegliche Art von Emotionen im Sport spielen vor allem in Wettkampfsituationen eine bedeutende Rolle, wenn es darum geht, zu einem bestimmten Zeitpunkt die optimale Leistung abzurufen. Emotionen können Auswirkungen auf der physiologischen, perzeptuell-kognitiven oder behavioralen Ebenen haben. Daher bildet den Schwerpunkt des vorliegenden Scoping-Reviews, die Untersuchung der Bedeutung wettkampfbezogener (state) Emotionen von Sporttreibenden. Die Literaturrecherche ergab 1126 Arbeiten, aus denen 15 Studien die Einschlusskriterien erfüllten. Diese wurden hinsichtlich ihrer Themenschwerpunkte betrachtet: 1) Emotionen, Kognitionen und Angst; 2) Emotionen, Leistungsbeurteilung und Stress; 3) Emotionen und Leistungsziele; 4) Unterschiede emotionaler Ausprägung im Geschlecht und Leistungsniveau; 5) Einfluss von Kausalzuschreibungen auf die Emotionen. Anschließend wurden die in den vorgestellten Studien verwendeten emotionserfassenden Messinstrumente betrachtet und vorgestellt. Zusammengefasst erscheint die Erfassung wettkampfbezogener (state) Emotionen rund um das sportliche Geschehen (vor, während, danach) ein wesentlicher Bestandteil der angewandten Sportpsychologie, davon abgeleiteter Emotionsregulationsstrategien und somit der optimalen Leistungserbringung zu sein, auch wenn der (deutschsprachigen) sportpsychologischen Praxis bisher nur begrenzte validierte Messinstrumente vorliegen.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Examining the Perceptual-Cognitive Mechanism of Deceptive Actions in Sports - Polzien, Andrea; Güldenpenning, Iris; Weigelt, Matthias (Experimental Psychology)
Abstract. In several kinds of sports, deceptive actions are used to hinder the anticipation performance of an opponent. During a head fake in basketball, a player turns the head to one side but passes the ball to the other side. A pass with a head fake generates a head-fake effect in the observer, which is characterized by slower and more error-prone responses to the pass direction as compared to passes without a head fake. Whereas the head-fake effect has been replicated several times, the question of its origin with dynamic stimuli has not been answered yet. The present study includes four experiments, which are conducted to examine the perceptual-cognitive mechanism underlying the effect by using the model of dimensional overlap ( Kornblum et al., 1990 ) and the additive factors logic ( Sternberg, 1969 ). Results point to multiple processes contributing to the head-fake effect for dynamic stimuli, which operate not only at a perceptual level but also at a level of response selection.
Keywords: General Psychology; Arts and Humanities (miscellaneous); Experimental and Cognitive Psychology; General Medicine

A question of (perfect) timing: A preceding head turn increases the head-fake effect in basketball - Polzien, Andrea; Güldenpenning, Iris; Weigelt, Matthias (Plos one)

Neural Correlates of Augmented Feedback Processing are Associated to Short-Term Behavioral Changes and Automaticity in Motor Learning - Krause, Daniel; Margraf, Linda; Weigelt, Matthias

Predictive value of valence-dependent neural correlates of augmented feedback processing for behavioral adaptation and learning in extensive motor learning - Krause, Daniel; Margraf, Linda; Weigelt, Matthias

Neural Processing of Augmented Feedback is Valence-Dependent and Changes After Extensive Practice of a New Motor Task - Margraf, Linda; Krause, Daniel; Weigelt, Matthias

Changes in valence-dependent neural correlates of augmented feedback processing after extensive motor sequence learning - Margraf, Linda; Krause, Daniel; Weigelt, Matthias

Effects of an Intervention for Promoting Basic Motor Competencies in Middle Childhood - Strotmeyer, Anne; Kehne, Miriam; Herrmann, Christian (International Journal of Environmental Research and Public Health)
The development of motor competencies is necessary for participation in the culture of sport, exercise, and physical activity, which in turn supports the development of a healthy lifestyle. A lack of physical activity in childhood and deficits in motor performance emphasize the relevance of interventions for promoting basic motor competencies. However, there are research desiderata with regard to such interventions. This article describes an intervention program for promoting basic motor competencies in middle childhood (around 6 to 10 years of age). The intervention was investigated in a longitudinal study from June 2019 to January 2020 (n = 200; 58% girls, M = 8.84 years, SD = 0.63) at three primary schools. The intervention was conducted once a week in physical education (PE). The comparison group participated in regular PE. The intervention showed significant effects on basic motor competencies in object movement but not in self-movement. The results demonstrate that positive effects on basic motor competencies can be achieved with the help of a relatively simple intervention. Further longitudinal studies are desirable as a means of substantiating the results and developing evidence-based concepts to support children in their development in the best possible way.
Keywords: Health; Toxicology and Mutagenesis; Public Health; Environmental and Occupational Health

Repeating head fakes in basketball: Temporal aspects affect the congruency-sequence effect - Polzien, A.; Güldenpenning, Iris; Weigelt, Matthias (Abstracts of the 63rd Conference of Experimental Psychologists (TeaP))

Cognitive load reduces interference by head fakes in basketball - Güldenpenning, Iris; Kunde, W.; Weigelt, Matthias (Abstracts of the 63rd Conference of Experimental Psychologists (TeaP))

Der Einfluss von Kontextinformationen auf den Blicktäuschungseffekt im Basketball - Güldenpenning, Iris; Barkey, Thies; Jackson, Robin C.; Weigelt, Matthias (Talententwicklung und Coaching im Sport. Abstractband der 53. Jahrestagung der Arbeitsgemeinschaft für Sportpsychologie (asp))

Mental body rotation with egocentric and object-based transformations in different postures: standing vs. balancing - Budde, Kirsten; Jöllenbeck, Thomas; Barela, José A.; Figueiredo, Gabriella A.; Weigelt, Matthias (Brazilian Journal of Motor Behavior)
BACKGROUND: Previous studies suggest better visual-spatial processing when participants are tested in postures in which dynamic stability is challenged. The question arises if this is also true for the performance in mental body-rotation tasks (MBRT). AIM: Taking the embodied cognition approach into account, the first aim of the present study was to examine the potential influence of different demands on dynamic stability for two postures (parallel stand vs. tandem stand) on solving two versions of the MBRT, inducing either an object-based or an egocentric perspective transformation strategy. The second aim was to investigate if these different demands on dynamic stability are reflected in postural sway parameters. METHOD: Thirty participants (18 females and 12 males) were tested in the two MBRTs and in a control condition. All tasks were performed while standing on a balance beam in tandem stand and in a feet parallel position on a force plate. RESULTS: The results for response time and response error revealed effects of rotation angle and task, but no effect of posture. The analyzed Center of Pressure (CoP) data revealed a reduction of body sway during the MBRT for egocentric perspective transformations. CONCLUSION: The results indicate that participants performed better for egocentric than for object-based transformations and that the egocentric transformation leads to more postural stability than the object-based.

Mental body rotation with egocentric and object-based transformations in different postures: sitting vs. standing. - Budde, Kirsten; Barela, José A; Figueiredo, Gabriella A; Weigelt, Matthias (TeaP 2021 - Abstracts of the 63rd Conference of Experimental Psychologists.)

Neurocognitive and Neurophysiological Functions Related to ACL Injury: A Framework for Neurocognitive Approaches in Rehabilitation and Return-to-Sports Tests - Piskin, Daghan Yuksel; Benjaminse, Anne; Dimitrakis, Panagiotis; Gokeler, Alli (Sports Health: A Multidisciplinary Approach)
Context: Only 55% of the athletes return to competitive sports after an anterior cruciate ligament (ACL) injury. Athletes younger than 25 years who return to sports have a second injury rate of 23%. There may be a mismatch between rehabilitation contents and the demands an athlete faces after returning to sports. Current return-to-sports (RTS) tests utilize closed and predictable motor skills; however, demands on the field are different. Neurocognitive functions are essential to manage dynamic sport situations and may fluctuate after peripheral injuries. Most RTS and rehabilitation paradigms appear to lack this aspect, which might be linked to increased risk of second injury. Objective: This systematic and scoping review aims to map existing evidence about neurocognitive and neurophysiological functions in athletes, which could be linked to ACL injury in an integrated fashion and bring an extensive perspective to assessment and rehabilitation approaches. Data Sources: PubMed and Cochrane databases were searched to identify relevant studies published between 2005 and 2020 using the keywords ACL, brain, cortical, neuroplasticity, cognitive, cognition, neurocognition, and athletes. Study Selection: Studies investigating either neurocognitive or neurophysiological functions in athletes and linking these to ACL injury regardless of their design and technique were included. Study Design: Systematic review. Level of Evidence: Level 3. Data Extraction: The demographic, temporal, neurological, and behavioral data revealing possible injury-related aspects were extracted and summarized. Results: A total of 16 studies were included in this review. Deficits in different neurocognitive domains and changes in neurophysiological functions could be a predisposing risk factor for, or a consequence caused by, ACL injuries. Conclusion: Clinicians should view ACL injuries not only as a musculoskeletal but also as a neural lesion with neurocognitive and neurophysiological aspects. Rehabilitation and RTS paradigms should consider these changes for assessment and interventions after injury.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Hamstrings substitution via anteromedial portal with optional anterolateral ligament reconstruction is the preferred surgical technique for anterior cruciate ligament reconstruction: a survey among ESSKA members. - Vascellari, A; Grassi, A; Canata, GL; Zaffagnini, S; Gokeler, A; Jones, H (Knee Surg Sports Traumatol Arthrosc)

Sagittal knee kinematics in relation with the posterior tibia slope during jump landing after an anterior cruciate ligament reconstruction. - Keizer, MNJ; Hijmans, JM; Gokeler, A; Otten, E; Brouwer, RW (J Exp Orthop)

Healthy subjects with lax knees use less knee flexion rather than muscle control to limit anterior tibia translation during landing. - Keizer, MNJ; Hijmans, JM; Gokeler, A; Benjaminse, A; Otten, E (J Exp Orthop)

Functional progression milestones following anterior cruciate ligament reconstruction are more appropriate than time-based criteria: a survey among the ESSKA. - Vascellari, A; Gokeler, A; Grassi, A; Canata, GL; Zaffagnini, S; Jones, H (Knee Surg Sports Traumatol Arthrosc)

Younger age and hamstring tendon graft are associated with higher IKDC 2000 and KOOS scores during the first year after ACL reconstruction. - Magnitskaya, N; Mouton, C; Gokeler, A; Nuehrenboerger, C; Pape, D; Seil, R (Knee Surg Sports Traumatol Arthrosc)

Passing return to sports tests after ACL reconstruction is associated with greater likelihood for return to sport but fail to identify second injury risk. - Welling, W; Benjaminse, A; Lemmink, K; Gokeler, A (Knee)

Balance task difficulty affects postural sway and cortical activity in healthy adolescents. - Gebel, A; Lehmann, T; Granacher, U (Exp Brain Res)

Platelet-rich plasma (PRP) as therapy for cartilage, tendon and muscle damage - German working group position statement. - Tischer, T; Bode, G; Buhs, M; Marquass, B; Nehrer, S; Vogt, S; Zinser, W; Angele, P; Spahn, G; Welsch, GH; Niemeyer, P; Madry, H (J Exp Orthop)

The influence of motor tasks and cut-off parameter selection on artifact subspace reconstruction in EEG recordings - Anders, P; Müller, H; Skjæret-Maroni, N; Vereijken, B; Baumeister, Jochen (Medical & Biological Engineering & Computing)

Modulations of Inter-Hemispherical Phase Coupling in Human Single Leg Stance. - Lehmann, T; Büchel, D; Cockcroft, J; Louw, Q; Baumeister, Jochen (Neuroscience)

Electrocortical dynamics differentiate athletes exhibiting low- and high- ACL injury risk biomechanics. - Bonnette, S; Diekfuss, JA; Grooms, DR; Kiefer, AW; Riley, MA; Riehm, C; Moore, C; Barber Foss, KD; DiCesare, CA; Baumeister, Jochen; Myer, GD (Psychophysiology)

Exploring the phenomenological, environmental, and task-related aspects of the Yips in Tennis, Miniature Golf, Darts, and Archery. - Klämpfl, Martin; Lobinger, Babett; Lehmann, Tim (International Journal of Sport Psychology)

Differences in event-related potentials indicate differential use of mental rotation processes in parity judgements of humanoid and alphanumeric stimuli - Krause, Daniel; Richert, Benjamin; Weigelt, Matthias

Neuronale Korrelate der mentalen Rotation von menschlichen Figuren und alphanumerischen Stimuli - Krause, Daniel; Richert, Benjamin; Weigelt, Matthias

Physical activity and health promotion for nursing staff in elderly care: a study protocol for a randomised controlled trial - Otto, Ann-Kathrin; Pietschmann, Juliane; Appelles, Luisa-Marie; Bebenek, Michael; Bischoff, Laura L; Hildebrand, Claudia; Johnen, Bettina; Jöllenbeck, Thomas; Kemmler, Wolfgang; Klotzbier, Thomas; Korbus, Heide; Rudisch, Julian; et al. (BMJ Open)
Introduction Nursing staff is burdened by high workload and stress. Furthermore, heavy lifting, as well as transferring nursing home residents, cause lumbar tissue damage and back pain. Exercise intervention studies to reduce work-related problems are rare and the evidence for efficacy of studies among nurses is limited. Studies including targeted analysis of requirements are necessary to generate effective recommendations and tailored interventions for health promotion programmes. The purpose of this multicentred intervention study is to identify work-related problems, to implement health promotion programmes and to evaluate their effectiveness. Methods and analysis A randomised controlled trial will be conducted, including a total of 48 nursing home facilities in eight regions of Germany with an estimated sample size of 700 nurses. Standardised ergonomics and posture training (10 weeks, once a week for 20–30 min) and subsequently, back-fitness training (12 weeks, once a week for 45–60 min) will be administered. Following the implementation of standardised health promotion programmes, further demand-oriented interventions can be implemented. The perceived exposure to work-related demands, work-related pain in different parts of the body, health-related quality of life, perceived stress, work-related patterns of behaviour and experience, presentism behaviour, work environment as well as general needs and barriers to health promotion, will be assessed at baseline (pre-test), at 10 weeks (post-test, after ergonomics training), at 22 weeks (post-test, after back-fitness training) and at 34 weeks of the programme (follow-up). Ethics and dissemination The study was reviewed and approved by the local ethics committee of the University of Hamburg (AZ: 2018_168). The results of the study will be published in open-access and international journals. Furthermore, the results will be presented in the participating nursing homes and at national and international conferences. Trial registration number DRKS.de (DRKS00015241).
Keywords: General Medicine

Mental rotation and performance in basketball: effects of self-controlled and externally controlled time constraints on the processing and execution of tactic board instructions with varied orientations - Krause, Daniel; Weigelt, Matthias (German Journal of Exercise and Sport Research)
Abstract Purpose In sports games, tactical instructions are mostly presented on tactic boards under temporal constraints determined by the length of time outs (e.g., 20–60 s time outs in basketball) and coaches’ instructional behavior. Thus, instructions should be presented in a way that enables fast and errorless information processing. High affordances in visual–spatial transformation (e.g., mental rotation processes) might both impede information processing and decrease execution performance. The aim of this study was to scrutinize the effect of different orientations of visual tactical displays on observation time under self-paced conditions as well as to compare the effects on execution performance to those of externally paced conditions. According to the self-determination theory, self-control over observation time is assumed to increase performance. Methods In a mixed-factors design with two factors, 48 participants were instructed to execute a basketball playing pattern, which was presented on a virtual tactic board in one of five different spatial disparities to the players’ on-court perspective. The Self-Paced Group determined the observation time in a self-controlled manner, whereas in the Yoked Group observation times were externally controlled, i.e., the observation time was constrained to match that of the Self-Paced Group.. Results The self-controlled time for watching the pattern before execution was significantly shorter and spatial accuracy in pattern execution was significantly higher for low disparity between instruction perspective and on-court perspective. Self-control over observation time did not affect execution accuracy. Conclusion The orientation effects might be explained by interfering mental rotation processes that are necessary to transform the instructional perspective into the players’ egocentric perspective. According to these results, coaches should align their tactic boards to their players’ on-court viewing perspective.
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Mental body rotation with egocentric and object-based transformations in different postures: sitting vs. standing - Budde, Kirsten; Barela, José Angelo; Figueiredo, Gabriella Andreeta; Weigelt, Matthias (Brazilian Journal of Motor Behavior)
BACKGROUND: A detail of previous studies on mental rotation, which has not received any attention so far, relates to the testing situation of the participants. In nearly every study, participants were tested in a sitting posture (and not standing). However, when considering embodied cognition approaches on mental processes, participants may not be able to fully exploit these processes when performing mental rotation tasks in a sitting posture.
AIM: Therefore, the aim of the present study is to examine the potential influence of two different postures (sitting vs. standing), when solving mental body rotation tasks.
METHOD: Sixteen participants (6 females) were tested in two mental body-rotation tasks (MBRT), requiring either an object-based spatial transformation (based on a same-different judgment) or an egocentric transformation (based on a left-right judgment) in a sitting and in a standing posture. Reaction times and response errors were analysed in two three-way ANOVAs, with the factors orientation, task, and posture.
RESULTS: Results revealed an effect of orientation and task, indicating that participants performed better for egocentric than for object-based transformations. However, there was no effect of posture.
CONCLUSION: The different dynamics of postural control during sitting and standing do not induce different embodiment effects on mental rotation.
Keywords: General Engineering

The role of different directions of attention on the extent of implicit perception in soccer penalty kicking - Memmert, Daniel; Noël, Benjamin; Machlitt, Daniel; van der Kamp, John; Weigelt, Matthias (Human Movement Science)
Keywords: Experimental and Cognitive Psychology; Orthopedics and Sports Medicine; General Medicine; Biophysics

The Mental Rotation Ability of Expert Basketball Players: Identifying On-Court Plays - Weigelt, Matthias; Memmert, Daniel (Research Quarterly for Exercise and Sport)
Keywords: Nephrology; Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine; General Medicine

Neue Wege der Medizintechnik: RehaToGo - das Ganglabor am Körper - Jäger, M; Rühlemann, A; Kecskemethy, A; Pohl, N; Hoffmann, M; Jöllenbeck, Thomas; Hefter, H; Kaiser, T (Zeitschrift für Orthopädie und Unfallchirurgie)

Multimodal approach towards understanding the changes in the autonomic nervous system induced by an ultramarathon. - Vieluf, S; Scheer, V; Hasija, Tanuj; Schreier, PJ; Reinsberger, Claus (Res Sports Med)

Golf spielen gegen die Vergesslichkeit: Effekte des Erlernens der Sportart auf das Default Mode Netzwerk des Gehirns - Ströhlein, Julia Kristin; Vieluf, Solveig; van den Bongard, Franziska; Gölz, Christian Johannes; Reinsberger, Claus (B&G Bewegungstherapie und Gesundheitssport)
Zusammenfassung Einleitung Im Rahmen der Demenz vom Alzheimer-Typ (DAT) zeigt sich eine gestörte neuronale Netzwerkorganisation, welche sich unter anderem auch im Default Mode Netzwerk (DMN) widerspiegelt. Multimodale Interventionen, wie zum Beispiel Golf, können einen positiven Einfluss auf die funktionelle Integrität der Netzwerke haben. Methodik Im Rahmen einer Pilotstudie wurde der Einfluss des Erlernens der Sportart Golf bei sieben älteren Menschen (> 60 Jahre) mit subjektiven Gedächtnisbeschwerden auf die funktionelle Konnektivität des DMN untersucht. Die Probanden haben 22 Wochen unter Anleitung eines professionellen Golftrainers dreimal wöchentlich je 60 min trainiert. Vor (Messzeitpunkt 0, MZP0) und nach der Intervention (Messzeitpunkt 1, MZP1) wurde eine Elektroenzephalografie (EEG)-Messung unter Ruhebedingungen (resting-state) durchgeführt. Die EEG-Daten wurden mit einem Magnetresonanztomographie-Template koregistriert. Die Konnektivitätsanalyse wurde in 15 Regionen des DMN durchgeführt und im Längsschnitt verglichen. Dabei wurden die Frequenzbänder beta (14–29 Hz) und theta (5–7 Hz) berücksichtigt. Ergebnisse Nach der Intervention wurde eine höhere funktionelle Konnektivität im gesamten DMN bei 5 / 7 Teilnehmenden im beta Frequenzband bzw. bei 6 / 7 Probanden im theta Frequenzband zu MZP1 im Vergleich zu MZP0 gemessen. Im anterioren DMN war bei allen Probanden und Probandinnen die funktionelle Konnektivität im beta Frequenzband zu MZP1 im Vergleich zu MZP 0 höher, während sie im theta-Band bei 6 von 7 Teilnehmenden niedriger war. Im posterioren DMN war bei 6 von 7 (beta), bzw. 5 von 7 (theta) Probanden und Probandinnen die funktionelle Konnektivität zu MZP1 höher als zu MZP0. Spearman-Korrelationsanalysen zeigen zudem einen Zusammenhang zwischen der Teilnahmehäufigkeit und der prozentualen Veränderung der funktionellen Konnektivität im gesamten DMN des beta Frequenzbandes (r = 0,786, p = 0,036) und im anterioren DMN des theta Frequenzbandes (r = –0,821, p = 0,023). Fazit Auf Basis der vorliegenden Daten lässt sich vermuten, dass das Erlernen der Sportart Golf einen Einfluss auf das DMN haben könnte. Die Ergebnisse bilden die Grundlage für die Planung einer Studie mit einer größeren Kohorte und randomisierten kontrollierten Design.

Effects of force level and task difficulty on force control performance in elderly people - Strote, Caren; Gölz, Christian Johannes; Stroehlein, Julia Kristin; Haase, Franziska Katharina; Koester, Dirk; Reinsberger, Claus; Vieluf, Solveig (Experimental Brain Research)
Abstract As the proportion of people over 60 years of age rises continuously in westernized societies, it becomes increasingly important to better understand aging processes and how to maintain independence in old age. Fine motor tasks are essential in daily living and, therefore, necessary to maintain. This paper extends the existing literature on fine motor control by manipulating the difficulty of a force maintenance task to characterize performance optima for elderly. Thirty-seven elderly ( M = 68.00, SD = 4.65) performed a force control task at dynamically varying force levels, i.e. randomly changing every 3 s between 10%, 20%, and 30% of the individual’s maximum voluntary contraction (MVC). This task was performed alone or with one or two additional tasks to increase task difficulty. The force control characteristics accuracy, variability, and complexity were analyzed. Lowest variability was observed at 20%. Accuracy and complexity increased with increasing force level. Overall, increased task difficulty had a negative impact on task performance. Results support the assumption, that attention control has a major impact on force control performance in elderly people. We assume different parameters to have their optimum at different force levels, which remain comparably stable when additional tasks are performed. The study contributes to a better understanding of how force control is affected in real-life situations when it is performed simultaneously to other cognitive and sensory active and passive tasks.
Keywords: General Neuroscience

Sport and Physical Activity in Epilepsy. - van den Bogard, F; Hamer, HM; Sassen, R; Reinsberger, Claus (Dtsch Arztebl Int)

Autonomic nervous system changes detected with peripheral sensors in the setting of epileptic seizures. - Vieluf, S; Reinsberger, Claus; El Atrache, R; Jackson, M; Schubach, S; Ufongene, C; Loddenkemper, T; Meisel, C (Sci Rep)

Match Situations Leading to Head Injuries in Professional Male Football (Soccer)-A Video-Based Analysis Over 12 Years. - Beaudouin, F; Aus der Fünten, K; Tröß, T; Reinsberger, Claus; Meyer, T (Clin J Sport Med)

Neurology - Reinsberger, Claus (Injury and health risk management in sports - a guide to decision making)

Wirkungsmessung bei sozialen Sportprojekten im Kontext der Entwicklungszusammenarbeit: Methodische Überlegungen und Herausforderungen. - Petry, K.; Bauer, K.; Biermann, Marie (Sport im Kontext von internationaler Zusammenarbeit und Entwicklung: Perspektiven und Herausforderungen im Spannungsfeld von Wissenschaft, Politik und Praxis.)

Inklusion im Kinder- und Jugendsport unter besonderer Berücksichtigung der Heterogenitätsdimension Behinderung. - Radtke, Sabine; Adolph-Börs, Cindy (Vierter Deutscher Kinder- und Jugendsportbericht. Gesundheit, Leistung und Gesellschaft.)

The influence of motor tasks and cut-off parameter selection on artifact subspace reconstruction in EEG recordings - Anders, Phillipp; Müller, Helen Martha; Skjæret-Maroni, Nina; Vereijken, Beatrix; Baumeister, Jochen (Medical & Biological Engineering & Computing)
Advances in EEG filtering algorithms enable analysis of EEG recorded during motor tasks. Although methods such as artifact subspace reconstruction (ASR) can remove transient artifacts automatically, there is virtually no knowledge about how the vigor of bodily movements affects ASRs performance and optimal cut-off parameter selection process. We compared the ratios of removed and reconstructed EEG recorded during a cognitive task, single-leg stance, and fast walking using ASR with 10 cut-off parameters versus visual inspection. Furthermore, we used the repeatability and dipolarity of independent components to assess their quality and an automatic classification tool to assess the number of brain-related independent components. The cut-off parameter equivalent to the ratio of EEG removed in manual cleaning was strictest for the walking task. The quality index of independent components, calculated using RELICA, reached a maximum plateau for cut-off parameters of 10 and higher across all tasks while dipolarity was largely unaffected. The number of independent components within each task remained constant, regardless of the cut-off parameter used. Surprisingly, ASR performed better in motor tasks compared with non-movement tasks. The quality index seemed to be more sensitive to changes induced by ASR compared to dipolarity. There was no benefit of using cut-off parameters less than 10.
Keywords: Computer Science Applications; Biomedical Engineering

Modulations of Inter-Hemispherical Phase Coupling in Human Single Leg Stance - Lehmann, Tim; Büchel, Daniel; Cockcroft, John; Louw, Quinette; Baumeister, Jochen (Neuroscience)
Keywords: General Neuroscience

Körperspannung trainieren : auf die richtige Spannung kommt es an - Körperspannung als zentrale Lernvoraussetzung im (Gerät-)TurnenKörperspannung trainieren: auf die richtige Spannung kommt es an - Körperspannung als zentrale Lernvoraussetzung im (Gerät-)Turnen - Dörrer, Hans-Joachim; Köster, Carolin (Sportpädagogik)

The Head-Fake Effect in Basketball Is Based on the Processing of Head Orientation, but Not on Gaze Direction - Weigelt, Matthias; Güldenpenning, Iris; Steggemann-Weinrich, Yvonne (Psychology)
Keywords: General Earth and Planetary Sciences; General Environmental Science

Electrify your Game! Anodal tDCS Increases the Resistance to Head Fakes in Basketball - Friehs, Maximilian A.; Güldenpenning, Iris; Frings, Christian; Weigelt, Matthias (Journal of Cognitive Enhancement)
Keywords: General Medicine

Is the head-fake effect in basketball robust against practice? Analyses of trial-by-trial adaptations, frequency distributions, and mixture effects to evaluate effects of practice - Güldenpenning, Iris; Schütz, Christoph; Weigelt, Matthias; Kunde, Wilfried (Psychological Research)
Reactions to the pass of a basketball player performing a head fake are typically slower than reactions to a basketball player who passes without a head fake (i.e., head-fake effect). The present study shows that extensive practice reduces the head-fake effect in basketball. Additional analyses were conducted to explore the mechanism behind the reduced head-fake effect. First, we analyzed whether or not participants developed some control over the processing of irrelevant gaze direction, as indicated by specific trial-to-trial adaptations (i.e., congruency sequence effect). Second, we fitted the individual frequency distributions of RTs to ex-Gaussian distributions, to evaluate if practice specifically affects the Gaussian part of the distribution or the exponential part of the distribution. Third, we modeled individual RT distributions as the so-called mixture effects to examine whether the way irrelevant gaze direction impacts performance (either occasionally but massively or continuously but moderately) changes with practice. The analyses revealed that the effect of practice could not be explained with an increasing congruency-sequence effect. Also, it could not be found in the ex-Gaussian distributional analyses. The assumption that residual failure to inhibit the processing of the gaze direction in contrast to continuous failures to do so might favor mixed effects over uniform effects at later courses of practice could not be validated. The reduced head-fake effect thus is argued to source in participants’ general increasing ability to inhibit the processing of the task-irrelevant gaze direction information and/or in a priority shift of gaze processing to a processing of the pass direction.
Keywords: Arts and Humanities (miscellaneous); Developmental and Educational Psychology; Experimental and Cognitive Psychology; General Medicine

Social cues can impact complex behavior unconsciously - Schütz, Christoph; Güldenpenning, Iris; Koester, Dirk; Schack, Thomas (Scientific Reports)
Abstract In three experiments, we investigated the effect of unconscious social priming on human behavior in a choice reaction time task. Photographs of a basketball player passing a ball to the left/right were used as target stimuli. Participants had to respond to the pass direction either by a whole-body (complex) response or a button-press (simple) response. Visually masked stimuli, showing both a task-relevant cue (pass direction) and a task-irrelevant, social cue (gaze direction), were used as primes. Subliminal social priming was found for kinematic (center of pressure) and chronometric measures (response times): gaze direction in the primes affected responses to the pass direction in the targets. The social priming effect diminished when gaze information was unhelpful or even detrimental to the task. Social priming of a complex behavior does not require awareness or intentionality, indicating automatic processing. Nevertheless, it can be controlled by top-down, strategic processes.
Keywords: Multidisciplinary

Head-fake perception in basketball: the relative contributions of expertise, visual or motor training, and test repetition - Güldenpenning, Iris; Kunde, Wilfried; Weigelt, Matthias (International Journal of Sport and Exercise Psychology)
Keywords: Applied Psychology; Social Psychology

Processing deceptive information in sports: Individual differences for responding to head fakes depends on the attentional capability of the observer - Güldenpenning, Iris; Weigelt, Matthias; Memmert, Daniel; Klatt, Stefanie (Psychology of Sport and Exercise)
Keywords: Applied Psychology